Role of efflux pumps, their inhibitors, and regulators in colistin resistance - Ding, Yinhuan; Hao, Jingchen; Xiao, Weijia; Ye, Caihong; Xiao, Xue; Jian, Chunxia; Tang, Min; Li, Guangrong; Liu, Jinbo; Zeng, Zhangrui (Frontiers in Microbiology, 2023)
Colistin is highly promising against multidrug-resistant and extensively drug-resistant bacteria clinically. Bacteria are resistant to colistin mainly through mcr and chromosome-mediated lipopolysaccharide (LPS) synthesis-related locus variation. However, the current understanding cannot fully explain the resistance mechanism in mcr-negative colistin-resistant strains. Significantly, the contribution of efflux pumps to colistin resistance remains to be clarified. This review aims to discuss the contribution of efflux pumps and their related transcriptional regulators to colistin resistance in various bacteria and the reversal effect of efflux pump inhibitors on colistin resistance. Previous studies suggested a complex regulatory relationship between the efflux pumps and their transcriptional regulators and LPS synthesis, transport, and modification. Carbonyl cyanide 3chlorophenylhydrazone (CCCP), 1-(1-naphthylmethyl)-piperazine (NMP), and Phe-Arg-βnaphthylamide (PAβN) all achieved the reversal of colistin resistance, highlighting the role of efflux pumps in colistin resistance and their potential for adjuvant development. The contribution of the efflux pumps to colistin resistance might also be related to specific genetic backgrounds. They can participate in colistin tolerance and heterogeneous resistance to affect the treatment efficacy of colistin. These findings help understand the development of resistance in mcr-negative colistinresistant strains.